Avaliação da suplementação com caseína sobre o periodonto e osso mandibular de ratos alimentados com dieta padrão e dieta de cafeteria - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
Objective: To evaluate the effect of casein supplementation on the periodontium and mandibular bone of rats fed with standard diet and a cafeteria diet. Material and methods: 24 Wistar rats, divided into four experimental groups: normal diet (ND), normal diet with casein (NDC), cafeteria diet (CD) and cafeteria diet with casein (CDC). The NDC and CDC groups received 2 Ml of micellar casein from the 60th to the 90th day. At 90 days, the animals were ortho euthanized and materials were removed for analysis. Results: There was a difference (p <0.0001) in the adiposity index between animals DN, DNC, DC and DCC. There was a difference for the measurement of HDL cholesterol, which was lower in the DCC group (p <0.0196) and DCC with DN (p <0.0039). In the radiographic analyzes, there was no difference in relation to the pixel density, however, there was a difference in the size of the mandibular anterior portion between DCC and DNC (p <0.0196) and DCC and DN (p <0.0039). In histology, a reduction in blood vessels was observed, both in alveolar bone (p = 0.0033), furcation bone (p <0.0001) and periodontal ligament (p = 0.0001) in CDC. Conclusions: The cafeteria diet did not increase inflammation in the periodontium and alveolar bone resorption, and casein did not appear to significantly influence the analyzed parameters. Further studies should be conducted to establish therapeutic strategies for the management of obesity.
Keywords: Dieta de cafeteria; Proteína láctea; Caseína; Reabsorção óssea alveolar; Periodonto; Cafeteria diet; Dairy protein; Casein; Alveolar resorption; Periodontium; CNPQ::CIENCIAS DA SAUDE